Drug-induced gene expression profile changes in relation to intestinal toxicity: State-of-the-art and new approaches. (July 2019) - Rodrigues, Daniela; Souza, Terezinha; Jennen, Danyel G.J.; Lemmens, Lieve; Kleinjans, Jos C.S.; de Kok, Theo M.
Highlights: Drug-induced intestinal toxicity often leads to interruption of patients' therapies. Little is known about the molecular mechanisms underlying intestinal toxicity. 5-FU, TKIs and NSAIDs induce specific transcriptomic responses upon intestinal damage. Most perturbed genes are involved in cell cycle, apoptosis and DNA repair. Better understanding of intestinal toxicity will improve the safety of medicines. Abstract: One of the major complications that patients experience during pharmacological treatment is the occurrence of adverse drug reactions (ADRs). The most affected organs are the liver, kidney, heart and the gastrointestinal-immune system. In comparison to the other organs, less progress has been made on human‐relevant prediction of drug‐induced intestinal toxicity, evidencing current large data gaps. The most widely used drugs that are associated with intestinal damage include chemotherapeutics, such as 5-Fluorouracil or Tyrosine Kinase Inhibitors (TKIs), as well as non-steroidal anti-inflammatory drugs (NSAIDs). Chemotherapeutics are regarded as inducers of acute intestinal toxicity whereas NSAIDs are associated with chronic inflammation of the intestine. In view of the fact that only a few studies have been dedicated to studying cellular and genomic responses in relation to drug-induced intestinal ADRs, little is known about how intestinal toxicity develops after exposure to such drugs or which molecular mechanisms are involved. Therefore, new models and experiments are required to establish transcriptomic responses and alterations of molecular markers induced by different medicines. This review summarizes the available information about transcriptomic responses and biomarkers of toxicity induced by 5-FU, NSAIDS or TKIs in different experimental models. Future investigation should address the challenges in predicting intestinal toxicity induced by drugs and unveil specific gene expression profiles that can be applied in the development of safer drugs.